Gestión del talento humano por competencias en los colaboradores de la escuela de postgrado -UNAP de la ciudad de Iquitos, 2018 - Romero Flores, Jessica Janina (2019)
To know the characteristics of the management of human talent by competencies in the workers at the UNAP Graduate College on Iquitos city. The general objective of this work was to determine the characteristics of human talent management by competencies in the workers at the UNAP Graduate College on Iquitos city in 2018. Having as specific objectives: Identify the knowledge, detail the skills, specify the motivation and identify the attitude that occurs in the workers at the UNAP Graduate College on Iquitos city in 2018. This research was carried out during the months of October, November and December of the year 2018; the population under study was 20 workers, considering 100% of them for the survey. The main results indicate that the workers show a high degree of knowledge and are willing of new challenges, a high degree of skills and are willing to offer it for the benefit of the institution and a high degree of motivation to achieve its objectives when the institution recognizes their merits.